KARAKTERISTIK KIMIA DAN PROFIL ASAM AMINO TEPUNG IKAN SEMBILANG (Paraplotosus albilabris) DENGAN METODE PENANGANAN YANG BERBEDA - dhumoli_tampubolon dhumoli_tampubolon; sumarto_sumarto sumarto_sumarto; mery_sukmiwati mery_sukmiwati (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This research aims to determine the physico-chemical characteristics and amino acid profile from sembilang fish meal with different handling methods. This research is using experimental method. Different handling methods used in this study were S0 (fresh fish), S1 (powdered fishmeal stored at cold temperatures), and S2 (powdered fishmeal kept at freezing temperatures). The results showed that S1 was the best handling of fish meal with yield of 14.13%, white degree 75.43%, water absorption 58.6%, acidity 8.0% water content 8.66%, ash content of 2.10%, protein content 80.48%, 4.20% fat content, total essential amino acid 39.12%, and non-essential amino acids 48.87%.